PENGARUH KEPEMILIKAN MANAJERIAL TERHADAP PROFITABILITAS SERTA DAMPAKNYA TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2015 SAMPAI DENGAN 2017 - Windy Herprianingsih; Makhdalena Makhdalena; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to determine the influence of managerial ownership of profitability and its impact on the value of companies in manufacturing companies listed on the Indonesia Stock Exchange (IDX) period 2015 to 2017. The population of this research is a manufacturing company listed on the Indonesia Stock Exchange from 2015 to 2017 that has data on profitability and managerial ownership, as well as normal distribution data. This research uses secondary data sourced from the company's annual report. The technical analysis of the data used is track analysis with the help of SPSS (Statistical Package for Social Science) program. The results showed that managerial ownership has a positive effect on profitability. Profitability affects positively to the company’s valueKey Words: managerial ownership, profitability (ROE), and corporate values.